Menumbuhkan kerjasama siswa melalui model Cooperative Learning tipe numbered head together dalam pembelajaran Sejarah (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2022)
The background of the study is the lack of cooperation between the student’s ability to teach history. This problem can be studied with the action research methods to the research design and Taggart Kemmis models. The findings of the first cycle are that the ability to work in the possession of students is still in the stage quite well. This can be seen in the indicator to encourage participation and show appreciation & sympathy. Groups still charge those who can do something other than that; some members focus on mobile phones that do not follow the task process. The group division is too much also contributed to the lack of effectiveness of the work on the assignment. The results from the second cycle are cooperation skills possessed by students beginning there is a change to be good. It can be seen from the indicators to encourage participation and show appreciation and sympathy for the average student who gets a good score. Other indicators of students are still good and quite good. The findings of the third cycle are that the ability to work all achieve good scores. All indicators of cooperation, on average, scored well; in fact, some groups scored very well. This research concludes that cooperative learning type numbered head together learning can foster student cooperation in class XI IPS 1 SMAN 10 Bandung in 3 cycles. The recommendation of this study is to use this learning model, and teachers must prioritize time management in working on assignments and group divisions
Keywords: action research; cooperation; type numbered heads together